2011
DOI: 10.1063/1.3662924
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ideality factor of hydrogenated amorphous silicon p-i-n solar cells

Abstract: The performance of hydrogenated amorphous silicon (a-Si:H) p-i-n solar cells is limited, as they contain a relatively high concentration of defects. The dark current voltage (JV) characteristics at low forward voltages of these devices are dominated by recombination processes. The recombination rate depends on the concentration of active recombination centers and the recombination efficacy of each of these centers. The first factor causes the ideality factor of the devices to be non-integer and to vary with vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The error margin for m(V) was obtained by analysis of propagation of the measurement inaccuracies, and we found it to be about 3%. As shown by Kind et al [9], m(V) increases with voltage. They also observed that the m(V) curves are slightly dependent on the i-layer thickness.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…The error margin for m(V) was obtained by analysis of propagation of the measurement inaccuracies, and we found it to be about 3%. As shown by Kind et al [9], m(V) increases with voltage. They also observed that the m(V) curves are slightly dependent on the i-layer thickness.…”
Section: Resultsmentioning
confidence: 73%
“…Apparently, in this region the activation energy is independent of the i-layer thickness and the presence of a buffer layer. Kind et al [9] showed that the thermal ideality factor for this series was 2.09 ± 0.04, close to the value of 2. This value for the activation energy implies that the recombination efficacy peaks at the position where R σ n = p.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Samples were deposited in a multi-chamber RF-PECVD facility under identical conditions and characterized with appropriate equipment at Delft University of Technology. 19 Each device structure is as follows: TCO/p-aSiC:H/i-a-Si:H/n-a-Si:H/Al. The front contact is an Asahi U-(SnO 2 :F) type substrate with a textured surface.…”
Section: Methodsmentioning
confidence: 99%